Strategy for strengthening the communication competence of culinary entrepreneurs in Madura Island - Rachmad, Teguh Hidayatul; Fatchiya, Anna; Muljono, Pudji; Manalu, Maria B.F. (Universitas Bunda Mulia, 2025)
The high potential of culinary diversity lies in four districts on Madura Island, namely Bangkalan, Sampang, Pamekasan and Sumenep with various flavors and tastes that are unique to each district. Lack of competent communication between the four districts has an impact on the lack of increasing potential for gastronomic tourism on Madura Island. This research aims to analyze strategies for strengthening the competencies of culinary entrepreneurs in Madura Island to create business sustainability. Considering the significant potential of the culinary sector in this region, the study identifies challenges faced by culinary entrepreneurs, such as access to raw materials, marketing, and skill development.Through qualitative research methods, data was collected through interviews with culinary entrepreneurs and Madurese cultural figures, while also supported by quantitative data obtained from culinary entrepreneurs.. The findings indicate that competency strengthening can be achieved through cooking skills training, digital marketing, and financial management. Additionally, collaboration with educational institutions and non-governmental organizations (NGOs) can enhance the capacity of entrepreneurs. The study recommends the development of ongoing support programs and effective marketing strategies to improve the competitiveness of Madura's culinary entrepreneurs. With the implementation of these strategies, it is hoped that culinary businesses in Madura Island can adapt and thrive in a competitive business environment.